Community Participation in Development Planning: Building Sustainable Communities - Iriani Margayaningsih, Dwi (International Journal of Social Science, Education, Communication and Economics, 2024)
Community participation in development planning is essential for fostering sustainable growth and enhancing the quality of life within communities. This article explores the significance of involving local populations in the planning process, emphasizing that participatory approaches lead to more effective and relevant development outcomes. The introduction outlines the theoretical underpinnings of community participation and its historical context. The literature review discusses various models of participation, examining case studies where community involvement has successfully influenced development projects. The methodology section details the qualitative and quantitative approaches used to assess the impact of participatory planning on community development. The results and discussion highlight key findings that illustrate the benefits of community engagement, such as increased project success rates and improved community ownership. Finally, the conclusion emphasizes the necessity of incorporating community voices in development planning to create resilient and sustainable communities. This article aims to serve as a guide for policymakers, practitioners, and researchers interested in fostering inclusive development processes.